Pengaruh Iklan dan Personal Branding terhadap Elektabilitas Calon Walikota/Calon Wakil Walikota Padang Periode 2014-2019 - Wardi, Yunia - (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2015)
This study aims to analyze the effects of the Ballyhoo, Banner, Followers Board, Newspaper Advertisement and Personal Branding toward the Electability of the Candidate of the Mayor/Vice Mayor of Padang period 2014-2019. The sample size is 220 the Citizen of the Padang City. The research sample was selected by using the Area Sampling Method. The data was analysed by statistical test of the Multiple Linear Regression. The results of this research reveal that : (1) the Ballyhoo and Banner positively significantly affect Personal Branding of the Canditate of the Mayor/Vice Mayor of the Padang City period 2014-2019, whereas the Flowers Board, and the Newspaper Advertisement don’t affect the Personal Branding of the Mayor/Wice Mayor of Padang period 2014-2019;(2) the Ballyhoo, Banner, Newspaper Advertisement, and Flowers Board don’t affect the Electability of the Canditate of the Mayor/Vice Mayor of the Padang City period 2014-2019, whereas the Personal Branding positively significantly affect the Electabilty of the Canditate of the Mayor/Vice Mayor of the Padang City period 2014-2019.